Authenticity of Hadith: A Comparative Study of Classical Hadith Criticism and Modern Forensic Linguistics (Al-Aasar, 2025)
This study offers a comprehensive comparative analysis of Hadith authenticity through the dual lenses of classical Hadith criticism and modern forensic linguistics. It examines the methodological foundations of isnād evaluation, narrator reliability, and matn scrutiny alongside contemporary techniques such as linguistic profiling, corpus-based modelling, stylometric measurement, and forensic anomaly detection. By exploring convergences in textual coherence assessment and divergences in epistemic orientation, the research highlights complementary strengths that can inform a more robust, multidimensional authentication framework. The study argues that integrating classical epistemology with empirical linguistic analytics not only enhances the precision of textual verification but also preserves the ethical and hermeneutical integrity of the Islamic tradition.